Hypothermia in a Rural Setting: An Emergency Medicine Simulation Scenario - Zhou, Felix (Cureus, 2017)
Patients presenting with hypothermia in a rural emergency department can be quite challenging to manage without significant mortality and morbidity. Standard medical school curricula do not fully prepare trainees for the unique aspects of practice in northern rural and remote communities. Training opportunities on site may provide a solution to this lack of experience. However, these communities often have limited simulation-based resources and expertise for conducting and developing simulation scenarios. In this technical report, we outline a hypothermia simulation that utilizes only basic resources and is, thus, practical for rural and remote facilities. The aim of this report is to better equip trainees, clinicians, and emergency department staff who may encounter such a scenario in their practice. While the simulation is specifically designed for medical students, resident doctors, and emergency department staff, it could also be applicable in other low-resource settings, such as military bases, search and rescue stations, and arctic travel and tourism infirmaries.